Capacidade imunogênica de proteínas recombinantes de Pasteurella multocida obtidas através de transcritos expressos durante a infecção in vivo - Silva, Mayara Inácio Vincenzi da (2019)
Pasteurella multocida (P. multocida) is a Gram-negative coccobacillus, classified into five capsular types (A, B, D, E, and F). It causes a variety of serious illnesses in many hosts, and in pigs it is related to respiratory problems. Based on data from P. multocida pulmonary infection in swine, it was possible to select transcripts that induce an immune response, thus allowing the production of immunogens from recombinant proteins. Thus, the objective of this work was to verify the immunogenic capacity of Yersina A (YadA) adhesin proteins, periplasmic protein probably involved in high-affinity Fe2 + transport and trap-T family transporter of P. multocida by experimental immunization in mice. The genes were amplified by polymerase chain reaction (PCR) and directionally cloned into the pNF6- K vector and transformed into Escherichia coli (E. coli) BL21 (DE3). Protein expression was induced by the addition of isopropyl β-D-1-thiogalactopyranoside (IPTG) and purified by histidine tail system. The purified proteins were analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS_PAGE) and Western blotting using serum from infected pigs. Recombinant proteins were associated with adjuvant (aluminum hydroxide) and administered subcutaneously in mice divided into five groups: adhesin group (GA); Fetrans Group (GF) and Trap Group (GT). Animals from Group P. multocida (GPm) and Control Group (GC) were not treated with any immunogen, and received 0.9% saline by the same route. Two doses of each 21 day interval recombinant protein were administered and then the animals (GA, GF, GT and GPm), with blood samples scheduled the day before the first dose and 21 days after the second dose of the immunogen and were submitted challenge with suspension of P. multocida intranasally. After challenge, 60% of GPm animals died within 20 to 40 hours post challenge, while 100% of GA, GF and GT animals survived. Tissue changes in GPm were diffuse marked pulmonary congestion with pleural surface color change to dark red and swelling; microscopically there was marked perivascular suppurative inflammatory infiltrate. In animals previously immunized with recombinant proteins macroscopic alterations were observed only in the GA group with consolidation in the cranial portion of the lobes. Microscopically the groups GA, GF and GT presented slight alterations in the pulmonary tissue. The CG did not present macro or microscopic alterations. Myeloperoxidase (MPO) levels were higher in GPm than in GC, GA, GF and GT, suggesting a higher inflammatory effect in the non-immunized group. Serum IFN-γ and IL-6 concentrations increased about 60% in GT characterizing the first innate immune response line. Based on the results, it is concluded that the immunological potential of adhesin-YadA proteins, periplasmic protein probably involved in high affinity Fe2 + transport and trap-T family transporter, with a protective index of 100% of immunized animals.